The p3 peptides (Aβ17-40/42) rapidly form amyloid fibrils that cross-seed with full-length Aβ - Yao Tian; Andrea P. Torres-Flores; Qi Shang; Hui Zhang; Anum Khursheed; Bogachan Tahirbegi; Patrick N. Pallier; John H. Viles (Nature Communications)
Abstract The p3 peptides, Aβ17-40/42, are a common alternative cleavage product of the amyloid precursor protein, and are found in diffuse amyloid deposits of Alzheimer’s and Down Syndrome brains. The p3 peptides have been mis-named ‘non-amyloidogenic’. Here we show p340/42 peptides rapidly form amyloid fibrils, with kinetics dominated by secondary nucleation. Importantly, cross-seeding experiments, with full-length Aβ induces a strong nucleation between p3 and Aβ peptides. The cross-seeding interaction is highly specific, and occurs only when the C-terminal residues are matched. We have imaged membrane interactions with p3, and monitored Ca2+ influx and cell viability with p3 peptide. Together this data suggests the N-terminal residues influence, but are not essential for, membrane disruption. Single particle analysis of TEM images indicates p3 peptides can form ring-like annular oligomers. Patch-clamp electrophysiology, shows p342 oligomers are capable of forming large ion-channels across cellular membranes. A role for p3 peptides in disease pathology should be considered as p3 peptides are cytotoxic and cross-seed Aβ fibril formation in vitro.